Determinação do perfil toxigênico em Staphylococcus aureos e estafilococos coagulase-negativa isolados de recém-nascidos pela técnica de RT-PCR - Calsolari, Regina Adriana de Oliveira [UNESP] (2006)
The Staphylococcus spp. are often found in the hospital ambient, being associated with a large infection variety. Several factors of virulence are responsible for the Staphylococcus pathology, and the enter toxin originated from Staphylococcus and the TTST -1 (toxin of toxic shock syndrome) are accentuated among them. In this study, ninety Staphylococcus aureus patterns and ninety negative-coagulation of Staphylococcus patterns, isolated from different clinical materials, were examined by the PCR technique for the gene's research which encode the toxins originated from Staphylococcus A (sea), B (seb), C (sec-1 ), D (sed) and TTST -1 (tst). The patterns that appeared positives for the presence of one or more genes were tested by the production capacity of the respective toxins by the RT -PCR technique. In relation to ECN species, the S. epidermidis was isolated to a large frequency, corresponding to 71, 1% of the total of ECN examined patterns, as well as S. warneri (6, 7%), S. haemolyticus (5, 6%), S. hominis (5, 6%), S.lugdunensis (5, 6%)J S. simulans (3, 3%), S. saprophyticus (1, 1 % ) and S. Xylosus (1, 1 %). The results revealed a total of 108 toxicological patterns, corresponding to 59 (54, 6%) S. aureus patterns and 49 (45, 4%) ECN patterns with one or more toxicological genes. Among the ECN studied species, only the S. simulans type didn't present genes that encode toxins originated from Staphylococcus. TheS.aureus showed toxicological genes for ali the classes of examined toxins, while the ECN presented genes to the A (sea), B (seb) C (sec-1) and TSST -1 (tst) toxins. The sec-1 gene was the most found as well in S.aureus patterns as in ECN, while the seb gene was the most frequent in S. aureus. The detection of the toxin production by the RT -PCR technique revealed43 positive patterns, corresponding to 37 (86, 0% ) S.aureus patterns producers of EEA, EEB, EEC, EED, and/or TSST -1 and six (14, 0%) ECN patterns producers of EEA and EEC.